The legacy of the beast: patrilinearity and rupture in Zola's La Bête humaine and Freud's Totem and Taboo - Counter, A (Oxford University Press, 2008)
This article explores the legacy of primitive violence evoked by Zola and Freud in La Bête humaine (1890) and Totem and Taboo (1913) respectively, and attempts to show how Zola's and Freud's use of a paradigm of primitive aggression might be ideologically complicit with a violent inclination in their contemporaneous societies. This issue will be considered in its relations with the notions of patrilinearity and rupture, concepts which are integral to both texts, and which, it shall be argued, constitute in some sense the essence of patriarchy. Reading both writers through the prism of Deleuze's theory, patrilinearity itself will begin to appear as a series of ruptures rather than a continuous genealogy, a history of struggle which both perpetuates and conceals the dominance of violence. The ambivalence of Freud's and Zola's rendering of that violence will ultimately appear as an ethical challenge to the reader.